Learn Android Studio build Android apps quickly and effectively - Gerber, Adam; Craig, Clifton (Apress, 2015)
Learn Android Studio covers Android Studio and its rich tools ecosystem, including Git and Gradle: this book covers how Android Studio works seamlessly with Git, for source control, and Gradle, a build and test tool.